Semiotic open complex systems: Processes and behaviors. (17th August 2016) - Usó‐Doménech, Josep Lluis; Nescolarde‐Selva, Josué Antonio; Lloret‐Climent, Miguel; Fan, Meng
Abstract : An H‐system is a conceptual or semiotic model of reality formed in the mind of the subject. Understanding the behavior of the system means being able to infer causal relationships that explain this system to the Observer‐subject, and therefore having access to mechanisms to construct a mental or ontological mathematical model of the system under study. A process is a mechanism involving a series of successive operations between stimuli and responses. © 2016 Wiley Periodicals, Inc. Complexity 21: 388–396, 2016